Pengaruh Variasi Bahan Baku (Tempurung Kelapa, Sekam Padi, Serbuk Gergaji Kayu Karat) dan Komposisi Perekat Terhadap Sifat Fisis Briket - Tony Siagian; Irpansyah Siregar; Edisarman Hasibuan; Tengku Jukdin Saktisahdan; Intan Zahar; Bayu Purnama (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2025)
This study aims to analyze the effect of raw material variations and adhesive composition on the physical properties of biomass briquettes. Coconut shells, rice husks, and rubberwood sawdust were used as raw materials at several adhesive ratios. The briquette production process consisted of drying, mixing, molding, and compaction. Density, moisture content, and compressive strength were measured to evaluate product quality. The results show that both raw material type and adhesive composition influence the physical characteristics of briquettes. Coconut-shell briquettes produced the highest density and compressive strength, while rice-husk briquettes exhibited the highest moisture content. These findings indicate that the appropriate selection of raw materials and adhesive composition is essential to improve the quality of biomass briquettes as an environmentally friendly alternative fuel.